Modification of Screen Printed Carbon Electrode (SPCE) with Polypyrrole (Ppy)-SiO2 for Phenol Determination - Erasti Pratiwi; Ani Mulyasuryani; Akhmad Sabarudin (The Journal of Pure and Applied Chemistry Research, 2018)
Electrode modification on screen printed carbon electrode (SPCE) with polypyrrole (Ppy)-SiO2 was done by electropolymerization. Polypyrrole (Ppy)-SiO2 was used for phenol determination. The analysis of this material was done by using Scanning Electron Microscopy (SEM), cyclic voltammetry method and differential pulse voltammetry. In a cyclic voltammetry analysis, we used potential range of -1 to 1 V with Ag/AgCl comparator electrode at scan rate of 100 mV/sec, while in differential pulse voltammetry method the potential range was 0 to 1 V toward Ag/AgCl, the scan rate of 50 mV/sec, the pulse rate is 0,2 V and the pulse width is 50 ms. From the analysis result with SEM, cyclic voltammetry and differential pulse voltammetry method, Polypyrrole (Ppy) -SiO2 is the best material and can be used as phenol measurement.